Application of fluorescence spectroscopy for rapid and noninvasive quality determination of yoghurt ice cream using chemometrics. (2nd September 2019) - Muhammad, Niaz; Huma, Nuzhat; Sahar, Amna; Ahmad, Muhammad Haseeb; Rahman, Ubaid ur; Khan, Muhammad Azam; Ishaq, Anum
Abstract : The aim of this study was to explore the potential of fluorescence spectroscopy to determine the quality of yoghurt ice cream, prepared by adding different concentrations of yoghurt (10, 20, 30, 40, 50%). The addition of 50% of yoghurt showed the lowest pH and meltdown values, whereas the highest acidity and overrun rates were observed at the same concentration. Additionally, fluorescence spectra taken at varied emission and excitation ranges were preprocessed for baseline correction. The partial least square regression analysis on proposed excitation wavelengths (270 nm, 280 nm, 290 nm and 315 nm) showed effective prediction of various quality parameters of yoghurt ice cream.